how to solve 6-2(5-4)?

20 Answers

Relevance
  • 2 months ago

    6-2(5-4)

    =6 - 2(1)

    =6 - 2

    =4 answer//

    • Login to reply the answers
  • 2 months ago

    I mightbbe totally wrong but I would do 6-2 which is 4 and multiply that times 1 which is 5-4

    • Bear Grylls2 months agoReport

      This is indeed the totally wrong way to do it

    • Login to reply the answers
  • 2 months ago

    6-2(5-4)

    To solve, solve the one in parentheses first.

    6-2(1) because 5-4 = 1 (perform multiplication)

    6-2 because 2(1) = 2 (perform subtraction)

    4 because 6-2 = 4

    Lesson: PEMDAS

    • Login to reply the answers
  • Anonymous
    2 months ago

    the answer is 4 (use order of operations)

    • Login to reply the answers
  • How do you think about the answers? You can sign in to vote the answer.
  • 2 months ago

    6 - 2(5-4) =

    6 - 2(1) =

    6 - 2 =

    4.

    • Login to reply the answers
  • 2 months ago

    its 4. 6 - 2x1. It's how they taught us in school.

    Source(s): Common sense
    • Login to reply the answers
  • Como
    Lv 7
    2 months ago

    -

    6 - 2 x 1 = 4

    • Login to reply the answers
  • Anonymous
    2 months ago

    Do 5 - 4 inside the brackets first

    multiply 2 by what is inside the brackets.

    then subtract the above from 6

    4 is what you should get.

    • Login to reply the answers
  • 2 months ago

    6 - 2(5 - 4) = 6 - 2(1) = 6 - 2 = 4

    • Login to reply the answers
  • 2 months ago

    4. Parenthesis goes first so 5-5 = 1. Then multiplication goes next so 2(1) = 2. Finally 6 - 2 = 4. 

    • Login to reply the answers
Still have questions? Get your answers by asking now.